(untitled) (Research, Society and Development, 2021)
Objective: To map the extent and reach of evidence on improvement in maternal and child health and its impact on the practice of obstetric nurses. Method: Scoping review protocol according to the Joanna Briggs Institute Review’s Manual. Included researches on the improvement of maternal and child health and the impacts on the practices (concept) of obstetric nurses (participant) in health services (context). Searches will be carried out in the following databases: LILACS, BDENF, MEDLINE, EMBASE and SCOPUS, from October to January 2022, in Portuguese, English and Spanish. For the study selection stage, the review team will independently carry out the selection using a data extraction tool. Results: The data will be presented in a tabular, diagrammatic and descriptive way from the evidence found and gathered into categories for analysis in the thematic modality. Conclusion: It is expected to contribute to the reflective process on the qualification and valorization of the obstetric nurse’s care.